Akselerasi Peningkatan Budaya Membaca Sebagai Upaya Mengurangi Screen Time pada Anak PAUD Melati RW 05: Penelitian - Faisal Riza Rahman; Yuliati; Panca Wahyuningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Reading culture is a fundamental foundation for supporting the growth and development of preschool children. However, the rapid advancement of digital technology has created new challenges, particularly the increasing trend of excessive screen time. This community service program was conducted at PAUD Melati RW.5, Semarang City, aiming to accelerate the improvement of reading culture through structured, participatory, and sustainable literacy interventions. The study employed observation, interviews, and questionnaires involving 19 children, 2 teachers, and parents. Data analysis revealed that 73.7% of children spent more than two hours per day on digital devices, significantly exceeding WHO recommendations, while interest in physical books remained low. The interventions included digital literacy workshops for parents, interactive storytelling training for teachers, the establishment of an interactive reading corner, and the provision of literacy activity modules. The results indicated an increase in children’s reading interest, a decrease in average screen time, and stronger involvement of both parents and teachers in supporting early literacy. The findings imply that collaborative strategies involving families, schools, and communities can serve as an effective solution to foster a strong reading culture while reducing children’s dependency on gadgets.